Advanced Biomedical and Clinical Diagnostic and Surgical Guidance Systems XXI 2023
DOI: 10.1117/12.2648431
|View full text |Cite
|
Sign up to set email alerts
|

A combined fluorescence lifetime and depth imaging system for medical imaging and surgical guidance

Abstract: Fluorescence lifetime imaging (FLIM) is a valuable technique which can be used to provide label free contrast between different tissue types and provide information about their molecular makeup and local environment. FLIM systems based on single photon avalanche diode (SPAD) arrays are increasingly being used in applications such as medical imaging due to their high sensitivity and excellent temporal resolution [1]. Additionally, SPAD arrays are also commonly employed for time of flight (ToF) imaging technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…As mentioned previously, this group has recently demonstrated that time resolved SPAD sensors may be used to perform combined WFLIm and time of flight measurements to allow for simultaneous lifetime contrast and 3D scene reconstruction 5 , 15 . The means for doing so is by analysing the temporal position of the rising edge of the fluorescence signal for each pixel 5 .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…As mentioned previously, this group has recently demonstrated that time resolved SPAD sensors may be used to perform combined WFLIm and time of flight measurements to allow for simultaneous lifetime contrast and 3D scene reconstruction 5 , 15 . The means for doing so is by analysing the temporal position of the rising edge of the fluorescence signal for each pixel 5 .…”
Section: Resultsmentioning
confidence: 95%
“…1 c. The green/yellow sample (colorFabb fluorescent green) consisted of fluorophores distributed within a PLA/PHA matrix with fluorophores embedded, and the pink (Real Filament fluorescent pink) consisted of fluorophores distributed throughout a matrix of just PLA. Although the precise fluorophores used in these filaments has not been shared by the manufacturer, they offer excellent fluorescent intensity and lifetime contrast and have been used widely for WFLIm characterisation previously 4 , 5 , 15 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FLIMera camera and associated software are both commercially available and have previously been demonstrated to give highly accurate fluorescent lifetimes [ 29 , 32 ]. These filaments have previously been used in WFLIm using the same excitation and emission settings as are used in this work [ 9 , 28 ].…”
Section: Experimental Methods and Materialsmentioning
confidence: 99%
“…Most recently, the authors of the current paper used a 32 32 SPAD array in TCSPC mode to perform combined fluorescence lifetime and ToF imaging [ 28 ]. This work differed from the previous techniques detailed above, as it aimed to determine the distance of the sample surface to the camera as opposed to subsurface depth, allowing surface mapping of the sample.…”
Section: Introductionmentioning
confidence: 99%